Output Voltage Regulation for DC-DC Buck Converters: A Passivity-Based PI Design (2019)
This paper presents a global tracking passivity-based proportional-integral (PI) control for output voltage regulation of a DC-DC Buck converter. The proposed controller is based on passivity formulation since DC-DC Buck converter has a passive structure in open-loop. Additionally, the controller takes advantage of the PI actions to design a control law that guarantees asymptotically stability in the Lyapunov's sense under closed-loop operation. The proposed controller does not depend on the parameters, which makes it a robust controller. The robustness of the proposed controller is checked by comparing its dynamical performance in front of a conventional PID controller. All simulation results were fulfilled via MATLAB software. © 2019 IEEE.